A novel concept for grid Li-ion BESS safety: Integration of Vanadium-air flow battery technology in fire protection system. (October 2021) - Barelli, L.; Bidini, G.; Ottaviano, P.A.; Pelosi, D.; Perla, M.; Gallorini, F.; Serangeli, M.
Highlights: A new concept in prevention and protection of Li-ion BESS is proposed. Thermal runaway is a recurring high impact failure effect in battery storage systems. Li-ion battery integration with VAB to prevent fire with permanent oxygen reduction. System integration is favored by the low power and capacity VAB and the Li-ion BESS. 5 kW/120 kWh VAB can protect a 9.6 MW/3.8 MWh Li-ion ESS container module. Abstract: Li-ion battery is the most diffused technology among electrochemical energy storage systems. Installed capacity forecasts suggest a strong growth in the next years with renewable energy utilization to meet decarbonization purposes. Over 20 fire incidents in grid systems were reported during the last years in Korea and United States, with negative repercussions in market and safety. Thermal runaway results as the recurring high impact failure effect. A novel concept to prevent Li-ion battery fires in grid installations could be represented by the integration with Vanadium-air flow batteries (VAB), a hybrid energy storage system configuration capable of fire prevention through permanent oxygen reduction in the protected volume. This novel solution is presented and discussed with reference to the safety framework including standards, firefighting systems, batteries features, experimental findings and incidental experience. Protection strategy fundamentals, the limiting oxygen concentration to be achieved, system configuration and sizing are defined proving the feasibility of the application of VABs as oxygen reduction system. To guarantee safety conditions in commercial container modules for grid applications, the required VAB installed power is three orders of magnitude lower than the Li-ion battery, while VAB capacity is more than 30 times smaller. The occupied volume for the anolyte is two orders of magnitude smaller than the protected one.